Diels–Alder cycloadditions of N-arylpyrroles via aryne intermediates using diaryliodonium salts - Chen, Huangguan; Han, Jianwei; Wang, Limin (Beilstein Journal of Organic Chemistry, 2018)
With a strategy of the formation of benzynes by using diaryliodonium salts, a cycloaddition reaction of N-arylpyrroles with benzynes was reported. A wide range of bridge-ring amines with various substituents have been synthesized in moderate to excellent yields (35–96%). Furthermore, with a catalytic amount of TsOH·H2O, these amines can be converted into the corresponding N-phenylamine derivatives easily, which are potentially useful in photosensitive dyes.
Keywords: benzyne; cycloaddition; diaryliodonium salts; N-phenylamine; pyrrole

(untitled) - Baltazzi, E.; Krimen, L. I. (Chem. Rev., 1963)

(untitled) - Gholap, S. S. (Eur. J. Med. Chem., 2016)

(untitled) - Gryko, D. T.; Vakuliuk, O.; Gryko, D.; Koszarna, B. (J. Org. Chem., 2009)

(untitled) - Antilla, J. C.; Baskin, J. M.; Barder, T. E.; Buchwald, S. L. (J. Org. Chem., 2004)

(untitled) - Honraedt, A.; Raux, M.-A.; Grognec, E. L.; Jacquemin, D.; Felpin, F.-X. (Chem. Commun., 2014)

(untitled) - Wen, J.; Zhang, R.-Y.; Chen, S.-Y.; Zhang, J.; Yu, X.-Q. (J. Org. Chem., 2012)

(untitled) - Liu, Y.-X.; Xue, D.; Wang, J.-D.; Zhao, C.-J.; Zou, Q.-Z.; Wang, C.; Xiao, J. (Synlett, 2013)

(untitled) - Ackermann, L.; Dell’Acqua, M.; Fenner, S.; Vicente, R.; Sandmann, R. (Org. Lett., 2011)

(untitled) - Morimoto, K.; Ohnishi, Y.; Koseki, D.; Nakamura, A.; Dohi, T.; Kita, Y. (Org. Biomol. Chem., 2016)

(untitled) - Kitamura, T.; Yamane, M. (J. Chem. Soc., Chem. Commun., 1995)

(untitled) - Sundalam, S. K.; Nilova, A.; Seidl, T. L.; Stuart, D. R. (Angew. Chem., Int. Ed., 2016)

(untitled) - Stuart, D. R. (Synlett, 2017)

(untitled) - Wang, M.; Huang, Z. (Org. Biomol. Chem., 2016)

(untitled) - Stridfeldt, E.; Lindstedt, E.; Reitti, M.; Blid, J.; Norrby, P.-O.; Olofsson, B. (Chem. – Eur. J., 2017)

(untitled) - Yoshimura, A.; Fuchs, J. M.; Middleton, K. R.; Maskaev, A. V.; Rohde, G. T.; Saito, A.; Postnikov, P. S.; Yusubov, M. S.; Nemykin, V. N.; Zhdankin, V. V. (Chem. – Eur. J., 2017)

(untitled) - Robidas, R.; Guérin, V.; Provençal, L.; Echeverria, M.; Legault, C. Y. (Org. Lett., 2017)

(untitled) - Caster, K. C.; Keck, C. G.; Walls, R. D. (J. Org. Chem., 2001)

(untitled) - Davies, J. W.; Durrant, M. L.; Walker, M. P.; Belkacemi, D.; Malpass, J. R. (Tetrahedron, 1992)

(untitled) - Sumida, Y.; Kato, T.; Hosoya, T. (Org. Lett., 2013)

(untitled) - Chen, J.; Baire, B.; Hoye, T. R. (Heterocycles, 2014)

(untitled) - McManus, H. A.; Fleming, M. J.; Lautens, M. (Angew. Chem., Int. Ed., 2007)

(untitled) - Wolthuis, E.; Jagt, D. V.; Mels, S.; De Boer, A. (J. Org. Chem., 1965)

(untitled) - Lin, C.; Zhen, L.; Cheng, Y.; Du, H.-J.; Zhao, H.; Wen, X.; Kong, L.-Y.; Xu, Q.-L.; Sun, H. (Org. Lett., 2015)

(untitled) - Li, P.; Wang, Z.; Song, C.; Zhang, H. (J. Mater. Chem. C, 2017)

(untitled) - Shaikh, A. M.; Sharma, B. K.; Chacko, S.; Kamble, R. M. (RSC Adv., 2016)

(untitled) - Piechowska, J.; Gryko, D. T. (J. Org. Chem., 2011)

(untitled) - Chen, H.; Gao, C.-H.; Jiang, Z.-Q.; Zhang, L.; Cui, L.-S.; Ji, S.-J.; Liao, L.-S. (Dyes Pigm., 2014)

(untitled) - Moorthy, J. N.; Venkatakrishnan, P.; Huang, D.-F.; Chow, T. J. (Chem. Commun., 2008)

(untitled) - Hofmann, S.; Hummert, M.; Scholz, R.; Luschtinetz, R.; Murawski, C.; Will, P.-A.; Hintschich, S. I.; Alex, J.; Jankus, V.; Monkman, A. P.; Lüssem, B.; Leo, K.; et al. (Chem. Mater., 2014)